Pilot study of head conformation changes over time in the Cavalier King Charles spaniel breed. (26th January 2019) - Knowler, Susan Penelope; Gillstedt, Lena; Mitchell, Thomas J; Jovanovik, Jelena; Volk, Holger Andreas; Rusbridge, Clare
Abstract : Modern interpretation of head conformation in the Cavalier King Charles spaniel (CKCS) has favoured a smaller, more exaggerated, brachycephalic type than originally described in the 1929 breed standard. Recent research studies identified brachycephaly and reduced hind cranium as two conformational (dysmorphic) features that increase risk for symptomatic Chiari‐like malformation and secondary syringomyelia (SM). A prospective pilot study investigated the hypothesis that dysmorphic head features could be assessed visually and correlated with risk of SM. Thirteen CKCS, selected from anonymised photographic evidence, were physically appraised by authorised Kennel Club judges using a head shape checklist. These subjective evaluations were then matched with objective measurements of the cranium (cephalic index and rostrocaudal doming) and their subsequent MRI. A positive correlation (P=0.039) between the judges' checklist score and rostrocaudal doming (hindskull ratio) and a positive correlation between the cephalic index and hindskull ratio (P=0.042) were identified. Five CKCS had no SM and their status tallied with 62 per cent of the judges' evaluation. Although the ability of adjudicators to identify differences in head conformation varied, there was sufficient association between the dysmorphic parameters and the risk of SM to cause concern and propose a larger study in CKCS breed.